Application of numerical methods for the study of the 2014 San Leo landslide (Northern Italy): challenges and lessons learned - Donati, Davide; Guerra, Cristiano; Bonaga, Gilberto; Ghirotti, Monica; Stead, Doug; Borgatti, Lisa (Italian journal of engineering geology and environment, 2024)
The 2014 San Leo landslide is a very peculiar landslide, being controlled by a large number of factors that interacted with each other; each one was in turn critical in driving, promoting, or allowing the slope failure. In the ten years after the landslide event, numerous studies were presented in the form of national and international journal articles, conference proceedings, as well as unpublished technical reports. These projects allowed different aspects and mechanisms to be investigated, progressively enhancing our understanding of the landslide. In this paper, we summarize, review, and discuss the various numerical modelling analyses that have been conducted, in order to outline the foundations on which future investigations may be designed. Considering the in depth understanding that has been gained on the geological, lithological, environmental, and engineering aspects of this site, we suggest that the San Leo plateau may be an ideal engineering geological field laboratory useful in investigating the evolution and instability phenomena that affect sites with similar characteristics within the Marecchia Valley region and beyond.